Detection And Study Of blaIMP Gene blaOXA Gene In Pseudomonas aeruginosa Isolates From Diabetic Foot Ulcers In Diabetic Patients - Malallah, Hiba. A.; Al-Mashhady, Fatima Radawi; AL-Kefaei, Ghadaq Hameed Neamah (Medical Science Journal for Advance Research, 2024)
Background: Diabetes mellitus is an acquired and/or inherited disease results from insulin deficiency or decrease effectively of the produced insulin; infection by Gram-negative bacteria in the wounds is common in patients with Diabetes mellitus, the wound dressing is very important for the treatment (P. aeruginosa) Pseudomonas aeruginosa which provided with factors OF genetic virulence. The objective of the current research is to identify the presence of the blaIMP and blaOXA genes in Pseudomonas aeruginosa bacteria that were isolated from diabetic individuals with diabetic foot ulcers. Approaches: A grand total of 120 skin grafts were harvested from patients with diabetic foot ulcers who visited Alsader medical city (September to January 2021) (males and females) at )20-70) years. Antibiotic resistance tests have been done for all specimens. Primary Identification depended on biochemical tests and Gram stain . Finally, Identification with Vitek 2 system was made. PCR for amplification required gene was performed, then gel electrophoresis to show amplified genes. Results: (83.3%) showed a positive culture of bacterial growth, while (16.7 %) showed a negative for culturing. So 17 (15.4%) Pseudomonas aeruginosa isolates . However, the percentage of blaOXA gene was (47%) in P. aeruginosa isolates while negative with blaIMP gene of P. aerginosa. Conclusion: Our investigation indicates that Pseudomonas aeruginosa is one of the primary causes of diabetic foot ulcers., and bacterial isolates showed the presence of blaOXA resistance gene, with the absence of blaIMP gene. These genes are one of the virulence factors and are partly antibiotic-resistant bacterium.